The Effect of Religiusity, Literacy and Income on Zakah Awareness in Baznas Tangerang City - Sabik Khumaini; M. Nurzansyah; Samsuri; Kamil Ali (PT FORMOSA CENDEKIA GLOBAL, 2023)
Islamic teachings recommend zakah as a tangible kind of social protection. It can act as a means of bridging the wealth gap between rich and impoverished Muslims, as well as between muzakki and mustahik. Therefore, there is no monopoly or wealth accumulation in a small number of Muslim groups. The goal of this study was to ascertain how income, literacy, and level of religiosity affected people's awareness of paying zakah in BAZNAS Tangerang City. This kind of study employs a quantitative methodology and a survey method with 100 participants. The traditional assumption test, which comprises the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, coefficient of determination test, F test, and t test, is used in the data analysis process. Considering the testthe Coefficient of Determination's (R2) findings. As can be observed, the adjusted R square value is 67.2%. This indicates that the dependent variable's variance can be described by the independent variable in 32.8% of cases, whereas 15.5% of the variance may be explained by other factors. Additionally, the F test results show that income, literacy, and religiosity all have a substantial beneficial impact on zakah awareness, with a level of significance less than 5%. While religiosity has a strong favorable impact on zakah awareness, the t test only partially supports this. Zakah awareness is significantly influenced positively by literacy and positively by income